Pendampingan Persalinan oleh Suami Berpengaruh terhadap Lama Persalinan Kala 1: Penelitian Kuasi Eksperiman - Elyasari, Elyasari; Feryani, Feryani; Aisa, Sitti; Arsulfa, Arsulfa (Health Information : Jurnal Penelitian, 2022)
Labor and the birth of a baby which is a happy moment for husband and wife. Labor and birth are influenced by various dimensional factors, namely the birth canal, strength, mother's position, and psychological response. A husband’s participation during the delivery process is deemed necessary and becomes part of intrapartum management. This study was a quasi-experimental study on pregnant women and their husbands who gave birth at health care facilities in Kendari City. The time for conducting the research was in May-November 2020. The research population was pregnant women in Kendari City with an average number of births of 50 people. The sampling technique used purposive sampling method, which was divided into two groups, a control group of 30 respondents, and a treatment group of 30 respondents. The treatment group was given the Delivery Assistance Module. The module contains activity material that is important to do while accompanying childbirth, especially the first stage of labor. The average pain score is relatively the same (6.57) in both groups. The average duration of the first stage of labor was shorter (5.53) than the control group (8.00). Statistical tests paired sample t-test on pain (p > 0.05) and length of labor (p < 0.05, t -2.437). Variables of pain and duration of labor in the first stage in the control group and the treatment group statistically had differences in each characteristic. Statistically, childbirth assistance by the husband is related to the duration of the first stage of labor.